Thioredoxin System Regulation in the Central Nervous System: Experimental Models and Clinical Evidence - Silva-Adaya, Daniela (Hindawi Publishing Corporation, 2014)
The reactive oxygen species produced continuously during oxidative metabolism are generated at very high rates in the brain. Therefore, defending against oxidative stress is an essential task within the brain. An important cellular system against oxidative stress is the thioredoxin system (TS). TS is composed of thioredoxin, thioredoxin reductase, and NADPH. This review focuses on the evidence gathered in recent investigations into the central nervous system, specifically the different brain regions in which the TS is expressed. Furthermore, we address the conditions that modulate the thioredoxin system in both, animal models and the postmortem brains of human patients associated with the most common neurodegenerative disorders, in which the thioredoxin system could play an important part.